Understanding heterogeneity of fetal hemoglobin induction through comparative analysis of F and A erythroblasts - Khandros, Eugene (Blood, 2020)
Reversing the developmental switch from fetal hemoglobin (HbF, α(2)γ(2)) to adult hemoglobin (HbA, α(2)β(2)) is an important therapeutic approach in sickle cell disease (SCD) and β-thalassemia. In healthy individuals, SCD patients, and patients treated with pharmacologic HbF inducers, HbF is present only in a subset of red blood cells known as F cells. Despite more than 50 years of observations, the cause for this heterocellular HbF expression pattern, even among genetically identical cells, remains unknown. Adult F cells might represent a reversion of a given cell to a fetal-like epigenetic and transcriptional state. Alternatively, isolated transcriptional or posttranscriptional events at the γ-globin genes might underlie heterocellularity. Here, we set out to understand the heterogeneity of HbF activation by developing techniques to purify and profile differentiation stage-matched late erythroblast F cells and non–F cells (A cells) from the human HUDEP2 erythroid cell line and primary human erythroid cultures. Transcriptional and proteomic profiling of these cells demonstrated very few differences between F and A cells at the RNA level either under baseline conditions or after treatment with HbF inducers hydroxyurea or pomalidomide. Surprisingly, we did not find differences in expression of any known HbF regulators, including BCL11A or LRF, that would account for HbF activation. Our analysis shows that F erythroblasts are not significantly different from non-HbF–expressing cells and that the primary differences likely occur at the transcriptional level at the β-globin locus.